The prevalence and correlates of information seeking anxiety in postgraduate students - Erfanmanesh, Mohammadamin; A., Abrizah; Abdul Karim, Noor Harun; Erfanmanesh, Mohammadamin; Abrizah, A.; Abdul Karim, Noor Harun (Malaysian Journal of Library and Information Science, 2017)
Erfanmanesh, M., Abrizah, A., & Karim, N. H. A. (2014). The prevalence and correlates of information seeking anxiety in postgraduate students. Malaysian Journal of Library & Information Science, Vol.19, no. 2: 69-82. This study aims to determine the prevalence and correlates of information seeking anxiety among a group of postgraduate students at a research-intensive university in Kuala Lumpur, Malaysia. The 38-item Information Seeking Anxiety Scale was administered to 375 postgraduate students drawn from a population of 11000 using stratified random sampling method. Results of the study revealed that information seeking anxiety is a prevalent phenomenon among postgraduate students. Different levels (low, mild, moderate and severe) of information seeking anxiety were reported to have experienced by 96.5% of the postgraduate students studied. Among the various demographic factors, gender, level of study, age and frequency of library use were found to be correlates of information seeking anxiety. Conversely, no associations were found between various subscales of the information seeking anxiety and nationality, information literacy skills instruction received, academic major and frequency of the Internet use. The implications of the findings are discussed.